Program Aplikasi Website Pemilihan Sepeda Motor Listrik Berdasarkan Metode TOPSIS di Wilayah Jakarta Barat - Ibnu Gunawan Prayogo; Hoiriah Hoiriah; Lukas Setia Udi; Hendrawan Hendrawan (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The rapid growth of Indonesia’s electric motorcycle market, particularly in West Jakarta, has made consumer decision-making more complex due to the many available alternatives and evaluation criteria. This study aims to develop a web-based decision support system (DSS) for selecting electric motorcycles using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Data were obtained through questionnaires distributed to 68 respondents with experience using electric motorcycles in West Jakarta, selected through purposive sampling based on the Cochran formula at a 90% confidence level. Six criteria were applied, namely purchase price, travel range, battery capacity, maximum speed, charging time, and after-sales service, all treated as benefit criteria according to the Likert-scale perception instrument. The system was developed using Next js, JavaScript, and a MySQL/MariaDB database. TOPSIS analysis ranked Polytron Fox 350 first with a preference value of 0.7938, followed by ALVA N3 and Honda CUV e:. Validation through unit, black-box, and end-to-end testing confirmed that the system outputs matched manual calculations.